On the geographical distribution and ecology of Pseudostaurosira cataractarum (Bacillariophyceae): new findings in the Palearctic and Neotropic ecozones - Grana, Lorena Giselle (2015)
The aim of this paper is to expand the current knowledge on the distribution, ecology and morphology of Pseudostaurosira cataractarum (Hustedt) C.E. Wetzel, E. Morales et Ector. We analysed several freshwater diatom assemblages within the Palearctic (Czech Republic, Europe) and Neotropic ecozones (Argentina and Bolivia, South America). In all localities, small araphids were the dominant or co-dominant group. Inside this group, P. cataractarum was only dominant in the samples from Argentina and Czech Republic, while the Bolivian samples had only a few individuals. RDA and PCA analyses show that the relative abundance of P. cataractarum was positively correlated with water conductivity. The following measurements resulted from the morphometric analysis, apical axis: 2.8–8.2 µm, transapical axis: 2.7–7.2 µm and stria density: 15–29 in 10 µm. In conclusion, the present is the first report of P. cataractarum for continental Europe (from fossil material) and the Neotropic ecozone (from extant populations). Besides having a preference for subaerial habitats, this taxon could be locally conditioned by water conductivity, although in each of the analysed samples this species was associated with cosmopolitan diatoms that are tolerant to a wide range of environmental conditions. Based on the morphometric analyses in studied populations, we propose that the size range for the apical and transapical axes of P. cataractarum should be expanded at the lower end of the range. Likewise, the range of stria density should be expanded since it is wider than that presented for the type population from Indonesia (Java). Consequently, an emended description is presented based on our study and on published data on type and fossil populations.